Research team-based learning: A new model for empowering students' research skills - Febblina Daryanes; Siti Zubaidah; Susriyati Mahanal; S. Sulisetijono (Universitas Muhammadiyah Malang, 2024)
Students' research skills still need to be empowered. The Research-Based Learning (RBL) model is reported to improve students' research skills, but it has weaknesses that need to be addressed. The Team-Based Learning model can accommodate the weaknesses of the RBL model and vice versa. The RBL and TBL models have advantages and disadvantages that complement each other. Therefore, this study aims to integrate the RBL and TBL models into a model that is expected to empower students' research skills. This study also ensures the model's validity, practicality, and effectiveness in empowering students' research skills by using validation sheets, observation sheets, response questionnaires, and student research skills questionnaires. The Plomp & Nieveen development model is used in this study. The developed model was tested on 40 students who had taken Environmental Science courses at the University of Riau. The findings show that the developed RTBL model with the stages of Preparing, Assessing Readiness, Researching in a Team, and Reflecting is valid based on the validator's assessment. The RTBL model is also practical and effective in improving research skills. The RTBL model developed can empower research skills and can be used by educators in the learning process.